Multi-unit renewables auctions for small markets - Designing the Danish multi-technology auction scheme. (February 2019) - Welisch, Marijke
Abstract: This paper investigates different criteria for the design of multi-unit renewable energy (RES) auctions in small markets. The multi-technology RES auctions which are to be implemented in Denmark in 2018 serve as an exemplary case for the assessment. Focus of the analysis is how setting the auction schedule and the auctioned volume per round impacts the auction outcomes, accounting for the particular challenges of small markets. Agent-based modelling of the Danish auctions scheme demonstrates that the Danish RES market provides sufficient competition to auction higher volumes and follow more ambitious expansion goals. Furthermore, with a fixed budget, it is more effective in terms of deployment achieved, to hold fewer auctions with a larger volume. A flexibility mechanism that allows up to 50% of the auction volume to be shifted between auction rounds to accommodate potential large-scale marginal bidders, proves to be a useful tool to increase deployment rates, without negatively affecting bid prices. Furthermore it was shown that at current cost levels, only onshore bidders would be awarded in the envisaged multi-technology scheme. Also, large-scale and multi-project bidders are likely to be most cost competitive - indicating that further measures to maintain diversity could be useful. Highlights: Volume and frequency have to be carefully balanced for RES auctions in small markets. A too small volume per round can deter especially large scale bidders and lower deployment. A flexible auction volume is suitable to maximise deployment rates. Further measures to avoid concentration in the long run are advised in Denmark. Currently, onshore wind and solar PV are not cost competitive in joint auctions in Denmark.